The Bible and the spade as E. Brenton’s way to save the poor - Olga Yablonskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article, through the activities of the English philanthropist E. Brenton, examines the problem of pauperization of the population of Great Britain in the 19th century, the causes of pauperization, the consequences and solutions are clarified. The results of the analysis of narrative sources and scientific literature are presented, reflecting the difficult socio-economic situation in the country and the activities of E. Brenton aimed at improving the lives of the poor and their children. The philanthropist notes the relationship between industrialization and the growth of unemployment, linking this with the displacement of man from the productive sphere by mechanisms. He rightly condemns the deep property differentiation of society, the unfair wages of workers, the system of enclosures that deprived the peasants of their land. Brenton saw the devastating consequences of pauperization in the spiritual degradation of people, the criminalization of the lower classes, the growth of crimes among minors. His articles criticize the existing system of helping the poor, workhouses, noting that they temporarily alleviated the situation of the poor and encouraged parasitism. E. Brenton developed ways to solve problems based on Christian spiritual values and the Christian principle of tireless work as "God's work". The author of the article comes to the conclusion that the eradication of poverty was utopia, with the help of the de-urbanization of the poor population of cities, the allocation of land in rural areas, the refusal to use mechanisms in the production of products. The program to save children from the city's slums was more realistic. E. Brenton rightly establishes the relationship between ignorance and the growth of deviations among minors. Its goal is to create a system of crime prevention through education, where the habits of hard work, order and Christian virtues were instilled in children. The paper considers the implementation of tasks through the "Society of Children's Friends" and schools. The author believes that the institutions of E. Brenton, where students received knowledge, religious, labor education, mastered professions, were effective in preventing delinquency and shaping the moral lifestyle of poor children, despite the failures in the implementation of the plan for labor emigration of minors to South Africa.